Biosorption of Methylene blue using clove leaves waste modified with sodium hydroxide - Heri Septya Kusuma; Uyiosa Osagie Aigbe; Kingsley Eghonghon Ukhurebor; Robert Birundu Onyancha; Benedict Okundaye; Ines Simbi; Onoyivwe Monday Ama; Handoko Darmokoesoemo; Bernadeta Ayu Widyaningrum; Otolorin Adelaja Osibote; Vincent Aizebeoje Balogun (Results in Chemistry, 2023)
Water pollution with carbon-based dyes is a critical environmental problem owing to the severe life-threatening issues associated with their ingestion by humans and the associated release of dye molecules into the ecosystem. Before being released into the environment, a number of techniques and technologies have been researched to remove dye and other harmful compounds from textile and industrial effluents. Currently, scientists are looking at the efficacy of new, low-cost, and biodegradable biomaterials for removing noxious pollutants like methylene blue (MB) from water bodies and the ecosystem. In this study, clove leaves (CL) activated with sodium hydroxide (NaOH) were employed as a bio-sorbent for the confiscation of MB. The produced CL-NaOH bio-sorbent was typified by employing Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) to ascertain the physiochemical properties of the CL-NaOH bio-sorbent. The response surface methodology (RSM) was employed to create a mathematical model and optimize the biosorption process of MB removal using activated CL-bio-sorbents using NaOH. Analysis of the variance (ANOVA) of the biosorption of MB showed the relative significance of the process parameters in MB confiscation. The biosorption process of MB to CL-NaOH bio-sorbent was perfectly defined utilizing the Freundlich (FRH), Langmuir (LNR) and pseudo-first-order (PFO) models. The established biosorption capacity was approximately 9.80 mg.g−1. Also, the calculated parameters of thermodynamics revealed that the biosorption of MB to the bio-sorbent was non-spontaneous and endothermic, with the process involving chemical sorption with high biosorption energy. Conclusively, this study reveals that the CL-NaOH bio-sorbent is a cost-efficient and recyclable bio-sorbent for the sequestration of MB from water-soluble solutions.